2023
DOI: 10.1096/fj.202300393r
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia: A key contributor to endothelial dysfunction in cardiovascular diseases

Abstract: As an end product of purine metabolism, uric acid (UA) is a major endogenous antioxidant in humans. However, impaired UA synthesis and excretion can lead to hyperuricemia (HUA), which may in turn induce endothelial dysfunction (ED) and contribute to the pathogenesis of cardiovascular diseases (CVDs; e.g., atherosclerosis and hypertension). In this review, we discuss recent advances and novel insights into the effects exerted by HUA conditions in ED and related underlying mechanisms focusing on impaired UA meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 118 publications
0
4
0
1
Order By: Relevance
“…Reduced uric acid excretion due to kidney disease can lead to hyperuricemia, which is an elevated level of uric acid in the blood [ 30 ]. Subsequently, elevated uric acid levels are known to be one of the risk factors for HF [ 31 , 32 ]. Gout, identified as one of the overall predictive factors, also represents a prominent symptom associated with elevated levels of uric acid [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced uric acid excretion due to kidney disease can lead to hyperuricemia, which is an elevated level of uric acid in the blood [ 30 ]. Subsequently, elevated uric acid levels are known to be one of the risk factors for HF [ 31 , 32 ]. Gout, identified as one of the overall predictive factors, also represents a prominent symptom associated with elevated levels of uric acid [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing recognition that hyperuricemia is a risk factor for CVD 40,41 with evidence that uric acid interferes with vascular endothelial function owing to mechanisms related to oxidative stress, inflammation, and reduced nitric oxide bioavailability. 129 Two prospective studies have investigated the association between PFAS and increased serum uric acid, with differing conclusions (Table 6;Figure). Both studies reported that PFOA was associated with increased serum uric acid.…”
Section: Serum Uric Acid and Hyperuricemiamentioning
confidence: 99%
“…Uric acid (UA), a scavenger of oxygen radical, is synthesized mainly in the liver, intestines, and the vascular endothelium as the end metabolite of purine, and excreted via the kidney/intestine. UA is involved in disorders of not only the kidney [ 86 ] , but also the liver [ 87 ] , the joint [ 88 ] , the brain [ 89 ] , and the cardiovascular system [ 90 ] via several mechanisms including oxidative stress, inflammation, and apoptosis. Well-known causes of serum hyperuricemia include UA metabolism disturbance and reduction of its secretion by kidney.…”
Section: Bioactive Molecules As Mediators Of the Microbiome-gut-liver...mentioning
confidence: 99%